Feasibility of interaortocaval clamping for renal artery during robot‐assisted right partial nephrectomy: A propensity score‐matching analysis. Issue 3 (9th February 2022) - Motoyama, Daisuke; Kawakami, Asuka; Sato, Ryo; Watanabe, Kyohei; Matsushita, Yuto; Watanabe, Hiromitsu; Ito, Toshiki; Sugiyama, Takayuki; Otsuka, Atsushi; Miyake, Hideaki
Abstract: Aim: To evaluate the impact of the interaortocaval clamping technique for the right renal artery on perioperative outcomes of patients who underwent robot‐assisted partial nephrectomy (RAPN). Methods: This study included 111 consecutive patients with right renal masses undergoing RAPN via the transperitoneal approach. In this series, standard and interaortocaval clamping techniques were defined as those for the right renal artery at the renal hilus and interaortocaval space, respectively. Based on the 3D images reconstructed from CT, interaortocaval clamping was preoperatively selected for patients in whom standard clamping of the main renal artery at the right hilum was judged to be technically difficult due to complicated vascular distribution, such as multiple branches of right renal arteries and veins and/or intertwining of these vessels. Results: Of 111 patients, 95 and 16 were classified into the standard and interaortocaval clamping groups, respectively, and interaortocaval clamping was uneventfully performed as planned in all 16. After adjusting patient variables by 1:3 propensity score‐matching, 33 and 11 patients were included in the respective groups, and there were no significant differences in major clinical characteristics between them, while the incidences of multiple branches of right renal vessels as well as their intertwining beside the right renal hilus were significantly higher in the interaortocaval clamping group. However, no significant difference was noted in any of the perioperative outcomes, including operative time or intraoperative blood loss, between the two groups. Conclusions: The interaortocaval clamping technique during RAPN is a feasible procedure with acceptable perioperative outcomes compared with standard hilar clamping, making it possible to more accurately resect renal tumors under clear visualization without unnecessary arterial bleeding from the tumor bed in patients with complex vascular distribution at the right renal hilus; however, special attention should be paid to the considerable individual variability of the interaortocaval anatomy.